Unlocking the power of sports: an exploration of the nexus between shared place, community competence, and sense of community - Räikkönen, Timo; Hedman, Juha (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The article introduces a novel conceptual framework that enables grasping the special qualities of sports and argues that current storytelling revolving around sports overshadows its true force in community building. By relying on Finnish pilot data, the paper builds a dialect between theory and practise, leading to identifying sports as a unique social space where communities come together. A shared place where individuals - in this case, adults engaged or involved in the collective action within local sports clubs - create and reinforce convivial interactions and community relationships, also enhancing their willingness and ability to address problems and opportunities collectively (i.e. community competence) and meet their needs for belonging and purpose (i.e. sense of community). Building on the developed conceptual framework and pilot data, the paper demonstrates how the special qualities of sports can be scrutinised and validated at the local level through empirical analysis and further harnessed into service of knowledge informed decision making. More generally, the paper offers means to (re)identify, (re)interpret, and (re)construct the central societal relationships within the field of sports, which in itself underscores sports' ability to cultivate profound connections, promote personal growth, and foster community cohesion within local communities.